TRADISI MANDI BALIMAU KASAI POTANG MOGANG DI KELURAHAN LANGGAM KECAMATAN LANGGAM KABUPATEN PELALAWAN - Hardyanti, Putri; Rosaliza, Mita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Â Mandi Balimau Kasai Potang Mogang is a unique tradition and has distinctive characteristics from Balimau bathing events in other regions. One of its uniqueness is the existence of the Tonggul Togak Ceremony which is one of a series of events before entering the peak of the Mandi Balimau ceremony. Tonggul itself has a meaning as a symbol of independence from every tribe in Langgam village. Another difference from the Mandi Balimau ceremony is that it is not permissible to bathe with men and women in the river because it is highly not recommended by the Traditional Elders of Langgam village. The Balimau Kasai Potang Mogang bathing event is carried out 4 days before the fasting month, as a symbol of self-purification before entering the holy month of Ramadan. Balimau itself means bathing with water mixed with oranges called limau (limes). Oranges that are commonly used are purut limes and mentimun limes, while kasai is made from a mixture of white rice, turmeric, lemongrass leaves, and lime leaves. In this study, the researcher used social system theory with a total of 7 informants consisting of ninik mamak (elders), religious leaders, community leaders, and regional officials. The results of the study show that the implementation of the potang mogang balimau kasai bathing tradition is still carried out to date and is supported by ninik mamak and regional officials. The meaning contained in Potang Mogang Balimau Bathing Tradition is the existence of social values, communication or interaction of the community that are well interwoven, elements of mutual interest, elements of family, and values of the sense of sharing.Â Â Keywords: Implementation, Mandi Balimau Kasai Potang Mogang, Meaning